Meta-Analysis of Safety Effect of Nitric Oxide Drugs on Acute Cerebral Hemorrhage - Akmal Zubair, Wajahat Nadeem, Sufian Rasheed, Tania Naveel, Sameen Fatima, MA. Socorro Gonzaga-Leong-On, Maria Binte Sarfraz, Nargis Sardar, Bakht Beland, Arsalan Rasheed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Nitric Oxide is involved in several physiological processes, including vasodilation, blood pressure control, platelet and antileucocyte activity, and neurotoxicity. When given within 4 to 6 hours after the start of stroke, nitric oxide donors (NO donors) have shown promise as an acute stroke therapy in two clinical studies. Methods: People with acute or chronic stroke were included in randomized trials of NO donors, and IPD was obtained from the trialists. The changed Rankin scale (mRS) and mortality by point in time to randomization were used to evaluate the impact of NO donor organize on practical result. Impairment, mood, and life quality were all included as secondary outcomes. Results: Glyceryl trinitrate (GTN) was used in all five studies (4,197 individuals). GTN reduced BP by 7.4/3.3mmHg as compare to the organize set. After 90 days, GTN has not altered any clinical measurements in any way, shape, or form. While GTN was linked with positive changes in the mRS (odds ratio (OR) of 0.52, 95% self-assurance gap of 0.34–0.78) and decreased mortality in 312 patients who were randomly assigned within 6 hours of the start of stroke, this was not the case for the other patients in the study. Conclusions: Little donors had no effect on the recovery of stroke victims. NO donors, on the other hand, may enhance outcomes in both ischemic and hemorrhagic stroke when specified in six hours of the start of stroke.